2022
DOI: 10.1007/s10989-021-10348-z
|View full text |Cite
|
Sign up to set email alerts
|

In silico Design and Characterization of Multi-epitopes Vaccine for SARS-CoV2 from Its Spike Protein

Abstract: COVID 19 is a disease caused by a novel coronavirus, SARS-CoV2 originated in China most probably of Bat origin. Multiepitopes vaccine would be useful in eliminating SARS-CoV2 infections as asymptomatic patients are in large numbers. In response to this, we utilized bioinformatic tools to develop an efficient vaccine candidate against SARS-CoV2. The designed vaccine has effective BCR and TCR epitopes screened from the sequence of S-protein of SARS-CoV2. Predicted BCR and TCR epitopes found antigenic, non-toxic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Antigenicity, allergenicity, toxicity, and solubility were also assessed for the final sequence of the designed vaccine, and it met all the criteria. The vaccine's antigenicity was confirmed by VaxiJen v2.0 servers 26 with a score of 0.6387 and ANTIGENpro 27 with a score of 0.9238, indicating the final vaccine had a high antigenicity. AllergenFP 1.0 and AllerTOP 2.0 servers 28 , 29 showed that the final vaccine is non-allergenic and does not induce allergic reactions.…”
Section: Resultsmentioning
confidence: 97%
“…Antigenicity, allergenicity, toxicity, and solubility were also assessed for the final sequence of the designed vaccine, and it met all the criteria. The vaccine's antigenicity was confirmed by VaxiJen v2.0 servers 26 with a score of 0.6387 and ANTIGENpro 27 with a score of 0.9238, indicating the final vaccine had a high antigenicity. AllergenFP 1.0 and AllerTOP 2.0 servers 28 , 29 showed that the final vaccine is non-allergenic and does not induce allergic reactions.…”
Section: Resultsmentioning
confidence: 97%
“…The interplay between SP and TLRs is complex and it is crucial to clarify the immunopathology of COVID-19. Molecular docking studies showed a direct interaction between human TLR4 (and TLR2) with SP on monocytes/macrophages (30,31,55,56), which induced proinflammatory responses in APCs (57). The silencing of TLR4 in monocytes and monocyte cell lines, as well as its molecular inhibition, clearly confirmed a tight S1-TLR4 interaction (58,59).…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, the same rSPs were able to induce the phosphorylation of NF-kB, strengthening the hypothesis of the possible role of surface TLR engagement (Figure 3B). Since in silico and structural studies indicated the direct interaction of rSP with TLR2 and TLR4 (30,31), we checked the direct binding of all VOC-rSPs to TLR2 or TLR4 stable-transfected HEK-293 cell lines. rSPs from all VOCs bound both TLR2 and TLR4 with different binding capacity: Wuhan and Delta-plus rSPs bound TLR4 more than TLR2, while the inverse occurred for G614-rSP (Figure 3C).…”
Section: Voc-rsps Activate Nk Cells Through Tlr2 and Tlr4 Engagementmentioning
confidence: 99%
“…The selected refined validated 3D structure of ORF1ab B-cell epitopes is subjected to Cluspro-.2 webserver: https://cluspro.org/home.php for analyzing the binding interaction with receptor TLR-3 (Kathwate, 2022).…”
Section: Molecular Docking Of Orf1ab and Receptor Tlr-3mentioning
confidence: 99%